Faculty development program to enhance teaching quality in construction - Rokooei, Saeed; Shojaei, Alireza; Ly, Reachsak (International journal of construction management, 2025)
This paper addresses the implementation of a faculty teaching development program to enhance the teaching skills of newly hired CME faculty in construction core subjects. The main objective of the study was to investigate to what extent CME faculty perceived various aspects and impacts of faculty development programs. This program was first conducted in the summer of 2022 in which 15 junior faculty participated in educational modules, presented by nationally recognized construction instructors. A quantitative survey was designed and distributed among the participants to gain their opinions and perceptions about the importance of faculty development and its potential effects on the enhancement of junior faculty teaching and mentorship skills. The results indicated a gap in the current CME academic practices as 27% of participants reported that their schools did not provide any mentorship program. This need was noticeable in the transition of newly hired faculty from their graduate programs to instructional academic careers. Also, the findings emphasized a significant potential (over 60% high or very high in all impact areas) for faculty development programs in CME. The findings of this study help CME scholars and administrators assiduously design and develop educational components to prepare their graduate students for academic positions.